The Effect of Job Satisfaction on Psychological Well-Being in School Teachers Luar Biasa (SLB) - Naimah, Hayatun; Dewi, Mahargyantari Purwani; Chrisnatalia, Maria (Devotion : Journal of Research and Community Service, 2025)
This study investigates the effect of job satisfaction on psychological well-being among Indonesian Special Needs School (SLB) teachers, a group facing unique professional demands. Despite prior research linking job satisfaction and well-being in general populations (e.g., Tenggara et al., 2008), SLB teachers remain understudied despite their critical role and challenges (Firmansyah & Widuri, 2014). Using purposive sampling, data from 116 SLB teachers were collected via Ryff’s Psychological Well-Being Scales and Job Satisfaction Survey, and analyzed through simple linear regression. Results confirmed a significant positive effect (p=0.000), with job satisfaction explaining 27.9% of well-being variance, while demographic factors (e.g., education level, marital status) further influenced outcomes. Psychological well-being was high overall, but job satisfaction averaged medium, highlighting gaps in institutional support. The study contributes to industrial-organizational and positive psychology literature by empirically validating this relationship in SLB teachers and suggesting targeted interventions (e.g., improved salaries, social support) to enhance their welfare.